Adhesive film for circuit connection, manufacturing method therefor, manufacturing method for circuit connection structure, and adhesive film accommodating set

The adhesive film with a photocured and thermoset composition addresses conductive particle flow and resistance issues, providing reliable circuit connections in high temperature and humidity conditions and maintaining storage integrity.

JP2025010576AActive Publication Date: 2025-01-22RESONAC CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024180254
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-13
Filing Date
2024-10-15
Publication Date
2025-01-22
Estimated Expiration
2040-03-10

AI Technical Summary

Technical Problem

Existing adhesive films for circuit connections face issues with conductive particle flow during manufacturing, leading to short circuits, deteriorated insulation properties, and variations in connection resistance, especially in high temperature and humidity environments, and storage conditions that can cause premature curing.

Method used

An adhesive film with a first adhesive layer made of a photocured and thermoset composition containing polymerizable compounds, photopolymerization and thermal polymerization initiators, and conductive particles, along with a second adhesive layer that suppresses conductive particle flow and maintains low connection resistance under high temperature and humidity.

Benefits of technology

The adhesive film effectively reduces conductive particle flow, maintains low connection resistance, and prevents peeling, ensuring reliable circuit connections even in harsh environments and during storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010576000001_ABST
    Figure 2025010576000001_ABST
Patent Text Reader

Abstract

To provide an adhesive film for circuit connection that can suppress the flow of conductive particles generated during the production of a circuit connection structure.SOLUTION: An adhesive film 1 for circuit connection comprises a first adhesive layer 2 and a second adhesive layer 3 laminated on the first adhesive layer 2, wherein the first adhesive layer 2 is composed of a photocured product of a photocurable thermosetting composition including a polymerizable compound, a photopolymerization initiator, a thermal polymerization initiator, and conductive particles 4, and the second adhesive layer 3 is composed of a thermosetting composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film for circuit connection and a method for producing the same, a method for producing a circuit connection structure, and an adhesive film storage set. [Background technology]

[0002] Conventionally, various adhesive materials have been used to connect circuits. For example, an adhesive film for circuit connection having anisotropic conductivity in which conductive particles are dispersed in the adhesive is used as an adhesive material for connecting a liquid crystal display and a tape carrier package (TCP), connecting a flexible printed circuit board (FPC) and a TCP, or connecting an FPC and a printed wiring board.

[0003] In the field of precision electronic devices in which anisotropically conductive circuit connection adhesive films are used, the density of circuits is increasing, and the electrode width and electrode spacing are becoming extremely narrow, making it no longer easy to efficiently capture conductive particles on microelectrodes and obtain high connection reliability.

[0004] In response to this, for example, Patent Document 1 proposes a method in which conductive particles are unevenly distributed on one side of an anisotropic conductive adhesive sheet, and the conductive particles are spaced apart from each other. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO 2005 / 54388 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the method of Patent Document 1, the conductive particles flow when the circuit is connected, so that the conductive particles may aggregate between the electrodes and cause a short circuit. In addition, the distribution of the conductive particles density caused by the flow of the conductive particles is likely to cause not only a decrease in insulation properties but also a variation in connection resistance value, so there is still room for improvement.

[0007] Therefore, the present invention aims to provide an adhesive film for circuit connection that can suppress the flow of conductive particles that occurs during the manufacture of a circuit connection structure, a method for manufacturing the same, a method for manufacturing a circuit connection structure using the adhesive film, and an adhesive film storage set that includes the adhesive film. [Means for solving the problem]

[0008] An adhesive film for circuit connection according to one aspect of the present invention comprises a first adhesive layer and a second adhesive layer laminated on the first adhesive layer, the first adhesive layer being made of a photocured product of a photo- and thermosetting composition containing a polymerizable compound, a photopolymerization initiator, a thermal polymerization initiator, and conductive particles, and the second adhesive layer being made of a thermosetting composition.

[0009] The adhesive film for circuit connection of the above aspect can suppress the flow of conductive particles that occurs during the manufacture of a circuit connection structure. Such an adhesive film for circuit connection can reduce the connection resistance between opposing electrodes of a circuit connection structure, and can maintain low connection resistance even in a high-temperature, high-humidity environment (e.g., 85°C, 85% RH). In other words, this adhesive film for circuit connection can improve the connection reliability of the circuit connection structure.

[0010] Incidentally, the adhesive film for circuit connection is required not to peel off from the circuit members even when the circuit connection structure is used for a long period of time under a high temperature and high humidity environment (e.g., 85°C, 85% RH) after the circuit members are connected. The above-mentioned adhesive film for circuit connection tends to be able to suppress peeling at the interface between the circuit members and the circuit connection part formed by the adhesive film, which occurs when the circuit connection structure is used under a high temperature and high humidity environment.

[0011] A method for producing an adhesive film for circuit connection according to one aspect of the present invention includes a preparation step of preparing a first adhesive layer, and a lamination step of laminating a second adhesive layer made of a thermosetting composition on the first adhesive layer, the preparation step including a step of irradiating a layer made of a photo- and thermosetting composition containing a polymerizable compound, a photopolymerization initiator, a thermal polymerization initiator, and conductive particles with light to cure the photo- and thermosetting composition to obtain a first adhesive layer. According to this method, it is possible to obtain an adhesive film for circuit connection that can suppress the flow of conductive particles that occurs during the production of a circuit connection structure.

[0012] The polymerizable compound may be a radically polymerizable compound having a radically polymerizable group, and may contain a radically polymerizable compound having a phosphate ester structure represented by the following formula (1). [ka] [In formula (1), n ​​represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.]

[0013] The thermosetting composition may contain a radically polymerizable compound having a radically polymerizable group.

[0014] The photoinitiator may have a structure shown in formula (I): [ka]

[0015] The structure represented by the above formula (I) may be an oxime ester structure, a bisimidazole structure or an acridine structure.

[0016] The photopolymerization initiator may contain a compound having a structure represented by formula (VI): [ka] [In formula (VI), R 11 , R12 and R 13 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing an aromatic hydrocarbon group.]

[0017] The thickness of the first adhesive layer may be 0.1 to 0.8 times the average particle size of the conductive particles.

[0018] A method for producing a circuit connection structure according to one aspect of the present invention includes the steps of interposing the above-mentioned adhesive film for circuit connection between a first circuit member having a first electrode and a second circuit member having a second electrode, and thermocompressing the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.

[0019] An adhesive film storage set according to one aspect of the present invention comprises the above-mentioned adhesive film for circuit connection and a storage member for storing the adhesive film, wherein the storage member has a visible portion that allows the inside of the storage member to be viewed from the outside, and the transmittance of light at a wavelength of 365 nm in the visible portion is 10% or less.

[0020] Generally, the environment in which the circuit connection adhesive film is used is a room called a clean room where the temperature, humidity, and cleanliness are controlled at a certain level, and when shipped from the production site, the circuit connection adhesive film is stored in a storage member such as a packaging bag to prevent it from being exposed directly to the outside air and causing quality deterioration due to dust and moisture. Usually, this storage member is provided with a viewing part made of a transparent material so that various information such as the product name, lot number, and expiration date affixed to the internal adhesive film can be confirmed from outside the storage member.

[0021] However, the inventors have found that when the above-mentioned circuit connection adhesive film is stored or transported in a conventional storage member and then used, the above-mentioned effects of the adhesive film may not be obtained. Based on these results, the inventors have further studied the adhesive film, and have found that when a compound capable of reacting with light and the photopolymerization initiator in the thermosetting composition is used as the polymerizable compound in the thermosetting composition, the thermosetting composition hardens during storage and transportation of the adhesive film, and the effect of reducing the connection resistance is reduced. Therefore, the inventors have further studied the adhesive film storage set based on the assumption that the polymerization of the polymerizable compound in the thermosetting composition is progressing due to the radicals derived from the photopolymerization initiator remaining in the first adhesive layer, and have found that the hardening of the thermosetting composition during storage or transportation can be suppressed by making the adhesive film storage set include the above-mentioned specific storage member, and the effect of reducing the connection resistance of the adhesive film can be maintained.

[0022] In other words, according to the adhesive film storage set of one aspect of the present invention, when a compound capable of reacting with light and a photopolymerization initiator in the thermosetting composition is used as the polymerizable compound in the thermosetting composition, the hardening of the thermosetting composition can be suppressed during storage or transportation of the adhesive film, and the effect of reducing the connection resistance of the adhesive film can be maintained. Effect of the Invention

[0023] According to the present invention, it is possible to provide an adhesive film for circuit connection that can suppress the flow of conductive particles that occurs during the manufacture of a circuit connection structure, and a manufacturing method thereof. Also, according to the present invention, it is possible to provide a manufacturing method of a circuit connection structure using such an adhesive film. Also, according to the present invention, it is possible to provide an adhesive film storage set including such an adhesive film. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an adhesive film for circuit connection according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a circuit connection structure according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a manufacturing process of a circuit connection structure according to one embodiment of the present invention. [Figure 4] FIG. 4 is a perspective view showing an adhesive film receiving set according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings as needed. In this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In addition, the upper limit and lower limit values ​​individually described can be arbitrarily combined. In addition, in this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". In addition, "(poly)" means both the case with and without the "poly" prefix.

[0026] <Adhesive film for circuit connection> Fig. 1 is a schematic cross-sectional view showing an adhesive film for circuit connection of one embodiment. As shown in Fig. 1, the adhesive film for circuit connection 1 (hereinafter also simply referred to as "adhesive film 1") comprises a first adhesive layer 2 and a second adhesive layer 3 laminated on the first adhesive layer 2.

[0027] (First adhesive layer) The first adhesive layer 2 is made of a cured product (photocured product) of a photo- and heat-curable composition. The photo- and heat-curable composition contains (A) a polymerizable compound (hereinafter also referred to as "(A) component"), (B) a photopolymerization initiator (hereinafter also referred to as "(B) component"), (C) a thermal polymerization initiator (hereinafter also referred to as "(C) component"), and (D) conductive particles 4 (hereinafter also referred to as "(D) component").

[0028] The first adhesive layer 2 is obtained, for example, by irradiating a layer made of a photo- and thermosetting composition with light energy to polymerize the (A) component and cure (photocure) the photo- and thermosetting composition. That is, the first adhesive layer 2 is made of conductive particles 4 and an adhesive component 5 obtained by photocuring the photo- and thermosetting composition. The adhesive component 5 contains at least a polymer of the (A) component. The adhesive component 5 may or may not contain unreacted (A) and (B) components.

[0029] [Component (A): Polymerizable compound] The component (A) is, for example, a compound that is polymerized by a radical, cation, or anion generated by a photopolymerization initiator upon irradiation with light (e.g., ultraviolet light). The component (A) may be any of a monomer, oligomer, and polymer. As the component (A), one type of compound may be used alone, or multiple types of compounds may be used in combination.

[0030] The (A) component has at least one polymerizable group. From the viewpoint of further improving the effect of reducing the connection resistance and achieving better connection reliability, the polymerizable group is preferably a radically polymerizable group that reacts with a radical. That is, the (A) component is preferably a radically polymerizable compound. Examples of the radically polymerizable group include a vinyl group, an allyl group, a styryl group, an alkenyl group, an alkenylene group, a (meth)acryloyl group, and a maleimide group. The number of polymerizable groups that the (A) component has may be 2 or more from the viewpoint of easily obtaining the physical properties and crosslinking density required for reducing the connection resistance after polymerization, and may be 10 or less from the viewpoint of suppressing the cure shrinkage during polymerization. From these viewpoints, the number of polymerizable groups that the (A) component has may be 2 to 10. Suppressing the cure shrinkage during polymerization is preferable in that a uniform and stable film (first adhesive layer) is obtained after light irradiation. In this embodiment, in order to balance the crosslink density and cure shrinkage, a polymerizable compound having the number of polymerizable groups within the above range may be used, and then a polymerizable compound having the number of polymerizable groups outside the above range may be additionally used.

[0031] Specific examples of the component (A) include (meth)acrylate compounds, maleimide compounds, vinyl ether compounds, allyl compounds, styrene derivatives, acrylamide derivatives, nadimide derivatives, natural rubber, isoprene rubber, butyl rubber, nitrile rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, and carboxylated nitrile rubber.

[0032] Examples of (meth)acrylate compounds include epoxy (meth)acrylate, (poly)urethane (meth)acrylate, methyl (meth)acrylate, polyether (meth)acrylate, polyester (meth)acrylate, polybutadiene (meth)acrylate, silicone acrylate, ethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, and 2-methylethyl (meth)acrylate. Acrylate, 2-hydroxyethyl (meth)acrylate, isopropyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobutyl (meth)acrylate, isobornyl (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, n-lauryl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate, N,N-di Methylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, polyethylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, neo Pentyl glycol di(meth)acrylate, pentaerythritol (meth)acrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid modified bifunctional (meth)acrylate, isocyanuric acid modified trifunctional (meth)acrylate, tricyclodecanyl acrylate, dimethylol-tricyclodecane diacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, 2,Examples include 2-di(meth)acryloyloxydiethyl phosphate and 2-(meth)acryloyloxyethyl acid phosphate.

[0033] Examples of the maleimide compound include 1-methyl-2,4-bismaleimidebenzene, N,N'-m-phenylene bismaleimide, N,N'-p-phenylene bismaleimide, N,N'-m-toluylene bismaleimide, N,N'-4,4-biphenylene bismaleimide, N,N'-4,4-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4-diphenylmethane bismaleimide, and N,N'-4,4-diphenylpropane. Examples of such maleimide include pan bismaleimide, N,N'-4,4-diphenyl ether bismaleimide, N,N'-3,3-diphenyl sulfone bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(3-s-butyl-4-8(4-maleimidophenoxy)phenyl)propane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)decane, 4,4'-cyclohexylidene-bis(1-(4maleimidophenoxy)-2-cyclohexyl)benzene, and 2,2'-bis(4-(4-maleimidophenoxy)phenyl)hexafluoropropane.

[0034] Examples of the vinyl ether compound include diethylene glycol divinyl ether, dipropylene glycol divinyl ether, cyclohexane dimethanol divinyl ether, and trimethylolpropane trivinyl ether.

[0035] Examples of the allyl compound include 1,3-diallyl phthalate, 1,2-diallyl phthalate, and triallyl isocyanurate.

[0036] From the viewpoint of obtaining an excellent balance between the curing reaction rate and the physical properties after curing, the component (A) is preferably a (meth)acrylate compound. From the viewpoint of obtaining better adhesive properties by achieving both the cohesive force for reducing the connection resistance and the elongation for improving the adhesive force, the component (A) may be a (poly)urethane (meth)acrylate compound. From the viewpoint of improving the cohesive force and further reducing the connection resistance, the component (A) may be a (meth)acrylate compound having a high Tg skeleton such as a dicyclopentadiene skeleton.

[0037] The (A) component may be a compound (e.g., polyurethane (meth)acrylate) in which a polymerizable group such as a vinyl group, an allyl group, or a (meth)acryloyl group is introduced into the terminal or side chain of a thermoplastic resin such as an acrylic resin, a phenoxy resin, or a polyurethane resin, from the viewpoint of balancing the crosslink density and the cure shrinkage, further reducing the connection resistance, and improving the connection reliability. In this case, the weight average molecular weight of the (A) component may be 3000 or more, 5000 or more, or 10,000 or more, from the viewpoint of excellent balance between the crosslink density and the cure shrinkage. In addition, the weight average molecular weight of the (A) component may be 1,000,000 or less, 500,000 or less, or 250,000 or less, from the viewpoint of excellent compatibility with other components. From these viewpoints, the weight average molecular weight of the (A) component may be 3,000 to 1,000,000, 5,000 to 500,000, or 10,000 to 250,000. The weight average molecular weight refers to a value measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the conditions described in the Examples.

[0038] The component (A) preferably contains, as a (meth)acrylate compound, a radically polymerizable compound having a phosphate structure represented by the following formula (1): In this case, the adhesive strength to the surface of an inorganic material (metal, etc.) is improved, making it suitable for bonding electrodes (for example, circuit electrodes). [ka]

[0039] In formula (1), n ​​represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.

[0040] The radical polymerizable compound having the phosphoric acid ester structure can be obtained, for example, by reacting phosphoric anhydride with 2-hydroxyethyl (meth)acrylate. Specific examples of the radical polymerizable compound having the phosphoric acid ester structure include mono(2-(meth)acryloyloxyethyl)acid phosphate, di(2-(meth)acryloyloxyethyl)acid phosphate, etc.

[0041] The content of the (A) component may be 5% by mass or more, 10% by mass or more, or 20% by mass or more based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of easily obtaining a crosslink density necessary for reducing connection resistance and improving connection reliability. The content of the (A) component may be 90% by mass or less, 80% by mass or less, or 70% by mass or less based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of suppressing curing shrinkage during polymerization. From these viewpoints, the content of the (A) component may be 5 to 90% by mass, 10 to 80% by mass, or 20 to 70% by mass, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition.

[0042] [Component (B): Photopolymerization initiator] The component (B) is a photopolymerization initiator (photoradical polymerization initiator, photocationic polymerization initiator, or photoanionic polymerization initiator) that generates radicals, cations, or anions upon irradiation with light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (e.g., ultraviolet light). From the viewpoint of facilitating curing at low temperature in a short time, the component (B) is preferably a photoradical polymerization initiator. As the component (B), one type of compound may be used alone, or multiple types of compounds may be used in combination.

[0043] Photoradical polymerization initiators are decomposed by light to generate free radicals. In other words, photoradical polymerization initiators are compounds that generate radicals by applying light energy from the outside. Examples of photoradical polymerization initiators include photopolymerization initiators having an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, an α-hydroxyalkylphenone structure, and the like.

[0044] From the viewpoint of further improving the effect of suppressing the flow of conductive particles and the effect of suppressing peeling, a photopolymerization initiator having a structure represented by the following formula (I) is preferably used as the component (B). The photopolymerization initiator may have a plurality of structures represented by the following formula (I). [ka]

[0045] The structure represented by the above formula (I) may be an oxime ester structure, a bisimidazole structure, or an acridine structure. That is, the photo- and thermosetting composition may contain a photopolymerization initiator having at least one structure selected from the group consisting of an oxime ester structure, a bisimidazole structure, and an acridine structure as the structure represented by the above formula (I). Among these, a photopolymerization initiator having an oxime ester structure is preferably used from the viewpoint of further improving the effect of suppressing the flow of conductive particles and the effect of suppressing peeling.

[0046] As the compound having an oxime ester structure, a compound having a structure represented by the following formula (VI) is preferably used. [ka]

[0047] In formula (VI), R 11 , R 12 and R 13each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing an aromatic hydrocarbon group.

[0048] Specific examples of compounds having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime), and the like.

[0049] Examples of compounds having a bisimidazole structure include 2,4,5-triarylimidazole dimers such as 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-phenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer, and 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer.

[0050] Examples of compounds having an acridine structure include 9-phenylacridine and 1,7-bis(9,9'-acridinyl)heptane.

[0051] The content of the photopolymerization initiator having the structure represented by the above formula (I) is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.45 mass% or more, particularly preferably 0.55 mass% or more, and extremely preferably 0.85 mass% or more, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of further improving the effect of suppressing the flow of the conductive particles. The content of the photopolymerization initiator having the structure represented by the above formula (I) is preferably 1.2 mass% or less, more preferably 0.9 mass% or less, and even more preferably 0.6 mass% or less, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of further improving the effect of suppressing peeling. From these viewpoints, the content of the photopolymerization initiator having the structure represented by the above formula (I) is preferably 0.1 to 1.2 mass%, more preferably 0.3 to 1.2 mass%, still more preferably 0.45 to 0.9 mass%, and particularly preferably 0.45 to 0.6 mass%, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition.

[0052] The content of the (B) component (total content of photopolymerization initiator) is preferably 0.3 mass% or more, more preferably 0.45 mass% or more, even more preferably 0.55 mass% or more, and particularly preferably 0.85 mass% or more, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of further improving the effect of suppressing the flow of the conductive particles. The content of the (B) component is preferably 1.2 mass% or less, more preferably 0.9 mass% or less, and even more preferably 0.6 mass% or less, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition, from the viewpoint of further improving the effect of suppressing peeling. From these viewpoints, the content of the (B) component is preferably 0.3 to 1.2 mass%, more preferably 0.45 to 0.9 mass%, and even more preferably 0.45 to 0.6 mass%, based on the total amount of components other than the conductive particles in the photo- and thermosetting composition.

[0053] [Component (C): Thermal polymerization initiator] The component (C) may be a thermal polymerization initiator that generates radicals, cations, or anions by heat (thermal radical polymerization initiator, thermal cationic polymerization initiator, or thermal anionic polymerization initiator), and is preferably a thermal radical polymerization initiator from the viewpoint of further improving the effect of reducing the connection resistance and achieving better connection reliability. As the component (C), one type of compound may be used alone, or multiple types of compounds may be used in combination.

[0054] The thermal radical polymerization initiator decomposes by heat to generate free radicals. That is, the thermal radical polymerization initiator is a compound that generates radicals by applying thermal energy from the outside. The thermal radical polymerization initiator can be arbitrarily selected from conventionally known organic peroxides and azo compounds. As the thermal radical polymerization initiator, from the viewpoint of further improving the flow suppression effect and the peeling suppression effect of the conductive particles, organic peroxides are preferable, and from the viewpoints of stability, reactivity and compatibility, organic peroxides having a one-minute half-life temperature of 90 to 175°C and a weight average molecular weight of 180 to 1000 are more preferable. By having the one-minute half-life temperature in this range, the storage stability is further excellent, the radical polymerizability is sufficiently high, and it can be cured in a short time.

[0055] Specific examples of component (C) include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, cumyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, and t-butyl peroxypi. Valate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneoheptanoate, t-amylperoxy-2-ethylhexanoate, di-t-butylperoxyhexahydroterephthalate, t-amylperoxy-3,5,5 -Trimethylhexanoate, 3-hydroxy-1,1-dimethylbutyl peroxyneodecanoate, t-amyl peroxyneodecanoate, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5 -Dimethyl-2,5-di(3-methylbenzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxybenzoate, dibutyl peroxytrimethyladipate, t-amyl peroxy normal octoate, t-amyl peroxy isononanoate, t-amyl peroxybenzoate, and other organic peroxides;Examples of azo compounds include 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanovaleric acid), and 1,1'-azobis(1-cyclohexanecarbonitrile).

[0056] The content of the (C) component may be 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more based on the total amount of components other than the conductive particles in the first adhesive layer from the viewpoint of excellent fast curing properties, and further improvement of the effect of suppressing the flow of the conductive particles and the effect of suppressing peeling. The content of the (C) component may be 20% by mass or less, 10% by mass or less, or 5% by mass or less based on the total mass of the first adhesive layer or the total amount of components other than the conductive particles in the first adhesive layer from the viewpoint of pot life. From these viewpoints, the content of the (C) component may be 0.1 to 20% by mass, 0.5 to 10% by mass, or 1 to 5% by mass based on the total amount of components other than the conductive particles in the first adhesive layer. The content of the (C) component based on the total amount of components other than the conductive particles in the photo- and thermosetting composition may be the same as the above range.

[0057] [(D) Component: Conductive particles] The component (D) is not particularly limited as long as it is a particle having electrical conductivity, and may be a metal particle composed of a metal such as Au, Ag, Ni, Cu, or solder, or a conductive carbon particle composed of conductive carbon. The component (D) may be a coated conductive particle having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), and a coating layer containing the above metal or conductive carbon and coating the core. Among these, metal particles formed of a heat-fusible metal, or coated conductive particles having a core containing a plastic and a coating layer containing a metal or conductive carbon and coating the core are preferably used. In this case, since the cured product of the photo- and thermosetting composition can be easily deformed by heating or pressure, when the electrodes are electrically connected to each other, the contact area between the electrodes and the component (D) can be increased, and the conductivity between the electrodes can be further improved.

[0058] The component (D) may be an insulating coated conductive particle comprising the above-mentioned metal particle, conductive carbon particle, or coated conductive particle, and an insulating layer containing an insulating material such as resin and coating the surface of the particle. When the component (D) is an insulating coated conductive particle, even if the content of the component (D) is high, the surface of the particle is coated with resin, so that the occurrence of a short circuit due to contact between the components (D) can be suppressed, and the insulation between adjacent electrode circuits can also be improved. The component (D) is used as one type of the above-mentioned various conductive particles alone or in combination of two or more types.

[0059] The maximum particle size of the (D) component must be smaller than the minimum distance between the electrodes (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and electrical conductivity, the maximum particle size of the (D) component may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and electrical conductivity, the maximum particle size of the (D) component may be 50 μm or less, 30 μm or less, or 20 μm or less. From these viewpoints, the maximum particle size of the (D) component may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of 300 arbitrary conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the largest value obtained is defined as the maximum particle size of the (D) component. In addition, when the (D) component is not spherical, such as having protrusions, the particle size of the (D) component is defined as the diameter of a circle circumscribing the conductive particle in the SEM image.

[0060] From the viewpoint of excellent dispersibility and conductivity, the average particle size of the (D) component may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the average particle size of the (D) component may be 50 μm or less, 30 μm or less, or 20 μm or less. From these viewpoints, the average particle size of the (D) component may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of 300 arbitrary conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the average value of the particle sizes obtained is defined as the average particle size.

[0061] The component (D) is preferably uniformly dispersed in the first adhesive layer 2. From the viewpoint of easily obtaining a stable connection resistance, the particle density of the component (D) in the first adhesive layer 2 is set to 100 pcs / mm 2 It may be more than 1000pcs / mm 2 More than 2000pcs / mm 2 From the viewpoint of improving the insulation between adjacent electrodes, the particle density of the (D) component in the first adhesive layer 2 is preferably 100,000 pcs / mm2 may be less than 50000pcs / mm 2 It may be less than 10000pcs / mm 2 From these viewpoints, the particle density of the component (D) in the first adhesive layer 2 may be 100 to 100,000 pcs / mm 2 1000~50000pcs / mm 2 2000 to 10000pcs / mm 2 It may be.

[0062] The content of the (D) component may be 0.1 volume % or more, 1 volume % or more, or 5 volume % or more based on the total volume in the first adhesive layer from the viewpoint of further improving the electrical conductivity. The content of the (D) component may be 50 volume % or less, 30 volume % or less, or 20 volume % or less based on the total volume in the first adhesive layer from the viewpoint of easily suppressing short circuits. From these viewpoints, the content of the (D) component may be 0.1 to 50 volume %, 1 to 30 volume %, or 5 to 20 volume % based on the total volume in the first adhesive layer. The content of the (D) component based on the total volume of the photo- and thermosetting composition may be the same as the above range.

[0063] [Other ingredients] The photo- and thermosetting composition may further contain other components in addition to the components (A), (B), (C) and (D). Examples of the other components include a thermoplastic resin, a coupling agent, a filler and a thermosetting resin. These components may be contained in the first adhesive layer 2.

[0064] Examples of the thermoplastic resin include phenoxy resin, polyester resin, polyamide resin, polyurethane resin, polyester urethane resin, and acrylic rubber. When the photo- and thermosetting composition contains a thermoplastic resin, the first adhesive layer can be easily formed. When the photo- and thermosetting composition contains a thermoplastic resin, the stress of the first adhesive layer generated during curing of the photo- and thermosetting composition can be alleviated. When the thermoplastic resin has a functional group such as a hydroxyl group, the adhesiveness of the first adhesive layer is likely to be improved. The content of the thermoplastic resin may be, for example, 5% by mass or more, 80% by mass or less, or 5 to 80% by mass based on the total amount of components other than the conductive particles in the photo- and thermosetting composition.

[0065] Examples of the coupling agent include silane coupling agents having organic functional groups such as (meth)acryloyl groups, mercapto groups, amino groups, imidazole groups, and epoxy groups, silane compounds such as tetraalkoxysilanes, tetraalkoxytitanate derivatives, and polydialkyltitanate derivatives. When the photo- and thermosetting composition contains a coupling agent, the adhesiveness can be further improved. The content of the coupling agent may be, for example, 0.1% by mass or more, 20% by mass or less, or 0.1 to 20% by mass based on the total amount of components other than the conductive particles in the photo- and thermosetting composition.

[0066] Examples of the filler include non-conductive fillers (e.g., non-conductive particles). When the photo- and thermosetting composition contains a filler, further improvement in connection reliability can be expected. The filler may be either an inorganic filler or an organic filler. Examples of the inorganic filler include inorganic fine particles such as metal oxide fine particles such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and nitride fine particles. Examples of the organic filler include organic fine particles such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles. These fine particles may have a uniform structure or a core-shell structure. The maximum diameter of the filler is preferably less than the minimum particle diameter of the conductive particles 4. The content of the filler may be, for example, 1% by volume or more, 30% by volume or less, or 1 to 30% by volume based on the total volume of the photo- and thermosetting composition.

[0067] A thermosetting resin is a resin that is cured by heat and has at least one thermosetting group. A thermosetting resin is, for example, a compound that crosslinks by reacting with a curing agent by heat. As the thermosetting resin, one type of compound may be used alone, or multiple types of compounds may be used in combination.

[0068] From the viewpoint of further improving the effect of reducing the connection resistance and achieving more excellent connection reliability, the thermosetting group may be, for example, an epoxy group, an oxetane group, or the like.

[0069] Specific examples of thermosetting resins include epoxy resins such as bisphenol-type epoxy resins which are reaction products of epichlorohydrin with bisphenol A, F, AD, or the like; epoxy novolac resins which are reaction products of epichlorohydrin with phenol novolac, cresol novolac, or the like; naphthalene-based epoxy resins having a skeleton containing a naphthalene ring; and various epoxy compounds having two or more glycidyl groups in one molecule, such as glycidyl amine and glycidyl ether.

[0070] The content of the thermosetting resin may be 30 mass % or more, 70 mass % or less, or may be 30 to 70 mass %, based on the total amount of components other than the conductive particles in the first adhesive layer.

[0071] When the first adhesive layer contains a thermosetting resin, the first adhesive layer may further contain a curing agent used to cure the thermosetting resin. The curing agent is not particularly limited as long as it is a curing agent that generates cationic species by heat, and can be appropriately selected according to the purpose. Examples of the curing agent include sulfonium salts and iodonium salts. The content of the curing agent may be, for example, 0.1 parts by mass or more, 50 parts by mass or less, or 0.1 to 50 parts by mass, relative to 100 parts by mass of the thermosetting resin.

[0072] The photo- and thermosetting composition may contain other additives such as softeners, accelerators, anti-degradants, colorants, flame retardants, and thixotropic agents. The content of these additives may be, for example, 0.1 to 10 mass % based on the total amount of components other than the conductive particles in the photo- and thermosetting composition. These additives may be contained in the first adhesive layer 2.

[0073] The first adhesive layer 2 may contain unreacted component (B). When the adhesive film 1 of the present embodiment is stored and transported in a conventional storage member, it is presumed that the unreacted component (B) remaining in the first adhesive layer 2 causes a part of the thermosetting composition in the second adhesive layer 3 to harden during storage and transport, thereby reducing the effect of reducing the connection resistance of the adhesive film 1. Therefore, when the first adhesive layer 2 contains component (B), the decrease in the effect of reducing the connection resistance can be prevented by storing the adhesive film 1 in a storage member described below.

[0074] The thickness d1 of the first adhesive layer 2 may be 0.1 times or more, 0.2 times or more, or 0.3 times or more of the average particle size of the conductive particles 4 from the viewpoint of making the conductive particles 4 more easily captured between the opposing electrodes and further reducing the connection resistance. The thickness d1 of the first adhesive layer 2 may be 0.8 times or less, or 0.7 times or less of the average particle size of the conductive particles 4 from the viewpoint of making the conductive particles more easily crushed when sandwiched between the opposing electrodes during thermocompression bonding and further reducing the connection resistance. From these viewpoints, the thickness d1 of the first adhesive layer 2 may be 0.1 to 0.8 times, 0.2 to 0.8 times, or 0.3 to 0.7 times the average particle size of the conductive particles 4. The thickness d1 of the first adhesive layer 2 refers to the thickness of the first adhesive layer located in the space between the adjacent conductive particles 4, 4.

[0075] When the thickness d1 of the first adhesive layer 2 and the average particle size of the conductive particles 4 satisfy the above-mentioned relationship, for example, as shown in FIG. 1, a part of the conductive particles 4 in the first adhesive layer 2 may protrude from the first adhesive layer 2 to the second adhesive layer 3 side. In this case, the boundary S between the first adhesive layer 2 and the second adhesive layer 3 is located in the space between the adjacent conductive particles 4, 4. By having the boundary S on the conductive particles along the surface of the conductive particles, the conductive particles 4 in the first adhesive layer 2 may satisfy the above-mentioned relationship without protruding from the first adhesive layer 2 to the second adhesive layer 3 side. The conductive particles 4 are not exposed on the surface 2a of the first adhesive layer 2 opposite to the second adhesive layer 3 side, and the opposite surface 2a may be a flat surface.

[0076] The relationship between the thickness d1 of the first adhesive layer 2 and the maximum particle size of the conductive particles 4 may be the same as above. For example, the thickness d1 of the first adhesive layer 2 may be 0.1 to 0.8 times the maximum particle size of the conductive particles 4, 0.2 to 0.8 times, or 0.3 to 0.7 times.

[0077] The thickness d1 of the first adhesive layer 2 may be appropriately set according to the height of the electrodes of the circuit members to be bonded. The thickness d1 of the first adhesive layer 2 may be, for example, 0.5 μm or more, 20 μm or less, or 0.5 to 20 μm. In addition, when a part of the conductive particles 4 is exposed from the surface of the first adhesive layer 2 (for example, protruding to the second adhesive layer 3 side), the shortest distance (distance shown as d1 in FIG. 1) from the surface 2a of the first adhesive layer 2 opposite to the second adhesive layer 3 side to the boundary S between the first adhesive layer 2 and the second adhesive layer 3 located in the space between the adjacent conductive particles 4, 4 is the thickness of the first adhesive layer 2, and the exposed part of the conductive particles 4 is not included in the thickness of the first adhesive layer 2. The length of the exposed part of the conductive particles 4 may be, for example, 0.1 μm or more, 20 μm or less, or 0.1 to 20 μm.

[0078] The thickness of the adhesive layer can be measured by the following method. First, the adhesive film is sandwiched between two pieces of glass (thickness: about 1 mm). Next, a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a hardener (product name: Epomount hardener, manufactured by Refine Tech Co., Ltd.) is cast. Then, the cross section is polished using a polishing machine, and the thickness of each adhesive layer is measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation).

[0079] (Second adhesive layer) The second adhesive layer 3 is made of, for example, a thermosetting composition containing (a) a polymerizable compound (hereinafter also referred to as component (a)) and (b) a thermal polymerization initiator (hereinafter also referred to as component (b)). The thermosetting composition constituting the second adhesive layer 3 is a thermosetting composition that can flow when a circuit is connected, and is, for example, an uncured thermosetting composition.

[0080] [Component (a): Polymerizable compound] The component (a) is, for example, a compound that is polymerized by a radical, cation, or anion generated by a thermal polymerization initiator by heat. As the component (a), the compounds exemplified as the component (A) can be used. From the viewpoint of facilitating connection at low temperature in a short time, further improving the effect of reducing the connection resistance, and providing superior connection reliability, the component (a) is preferably a radical polymerizable compound having a radical polymerizable group that reacts with a radical. Examples of preferred radical polymerizable compounds in the component (a) and combinations of preferred radical polymerizable compounds are the same as those for the component (A). When the component (a) is a radical polymerizable compound and the component (B) in the first adhesive layer is a photoradical polymerization initiator, the adhesive film is accommodated in a storage member described later, which tends to significantly suppress the curing of the thermosetting composition during storage or transportation of the adhesive film.

[0081] Component (a) may be any of a monomer, oligomer, or polymer. As component (a), one type of compound may be used alone, or multiple types of compounds may be used in combination. Component (a) may be the same as or different from component (A).

[0082] The content of the (a) component may be 10% by mass or more, 20% by mass or more, or 30% by mass or more based on the total mass of the thermosetting composition, from the viewpoint of easily obtaining a crosslink density necessary for reducing the connection resistance and improving the connection reliability. The content of the (a) component may be 90% by mass or less, 80% by mass or less, or 70% by mass or less based on the total mass of the thermosetting composition, from the viewpoint of being able to suppress the curing shrinkage during polymerization and obtaining good reliability. From these viewpoints, the content of the (a) component may be 10 to 90% by mass, 20 to 80% by mass, or 30 to 70% by mass based on the total mass of the thermosetting composition.

[0083] [Component (b): Thermal polymerization initiator] As the component (b), the same thermal polymerization initiator as the component (C) can be used. As the component (b), one type of compound may be used alone, or multiple types of compounds may be used in combination. The component (b) is preferably a thermal radical polymerization initiator. Examples of preferred thermal radical polymerization initiators for the component (b) are the same as those for the component (C).

[0084] The content of the (b) component may be 0.1 mass% or more, 0.5 mass% or more, or 1 mass% or more, based on the total mass of the thermosetting composition, from the viewpoint of further improving the effect of reducing the connection resistance and achieving better connection reliability. The content of the (b) component may be 30 mass% or less, 20 mass% or less, or 10 mass% or less, based on the total mass of the thermosetting composition, from the viewpoint of pot life. From these viewpoints, the content of the (b) component may be 0.1 to 30 mass%, 0.5 to 20 mass%, or 1 to 10 mass%, based on the total mass of the thermosetting composition.

[0085] [Other ingredients] The thermosetting composition may further contain other components in addition to the components (a) and (b). Examples of the other components include a thermoplastic resin, a coupling agent, a filler, a softener, an accelerator, an anti-degradation agent, a colorant, a flame retardant, a thixotropic agent, etc. Details of the other components are the same as those of the other components in the first adhesive layer 2.

[0086] The thermosetting composition may contain the above-mentioned thermosetting resin instead of the (a) component and the (b) component, or in addition to the (a) component and the (b) component. In this case, the thermosetting composition may contain a curing agent used to cure the above-mentioned thermosetting resin. When a thermosetting resin is used instead of the (a) component and the (b) component, the content of the thermosetting resin in the thermosetting composition may be, for example, 20% by mass or more, 80% by mass or less, or 20 to 80% by mass based on the total mass of the thermosetting composition. When a thermosetting resin is used in addition to the (a) component and the (b) component, the content of the thermosetting resin in the thermosetting composition may be, for example, 20% by mass or more, 80% by mass or less, or 20 to 80% by mass based on the total mass of the thermosetting composition. The content of the curing agent may be the same as the range described as the content of the curing agent in the photo- and heat-curable composition.

[0087] The content of the conductive particles 4 in the second adhesive layer 3 may be, for example, 1 mass % or less, or may be 0 mass %, based on the total mass of the second adhesive layer. It is preferable that the second adhesive layer 3 does not contain the conductive particles 4.

[0088] The thickness d2 of the second adhesive layer 3 may be appropriately set according to the height of the electrodes of the circuit members to be bonded. The thickness d2 of the second adhesive layer 3 may be 5 μm or more, 200 μm or less, or 5 to 200 μm, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability. In addition, when a part of the conductive particles 4 is exposed from the surface of the first adhesive layer 2 (for example, protruding toward the second adhesive layer 3 side), the distance (distance indicated by d2 in FIG. 1) from the surface 3a of the second adhesive layer 3 opposite to the first adhesive layer 2 side to the boundary S between the first adhesive layer 2 and the second adhesive layer 3 located in the space between the adjacent conductive particles 4, 4 is the thickness of the second adhesive layer 3.

[0089] The ratio of the thickness d1 of the first adhesive layer 2 to the thickness d2 of the second adhesive layer 3 (thickness d1 of the first adhesive layer 2 / thickness d2 of the second adhesive layer 3) may be 1 or more and 100 or less, from the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better reliability.

[0090] The thickness of the adhesive film 1 (the sum of the thicknesses of all layers constituting the adhesive film 1. In FIG. 1, the sum of the thickness d1 of the first adhesive layer 2 and the thickness d2 of the second adhesive layer 3) may be, for example, 5 μm or more, 200 μm or less, or may be 5 to 200 μm.

[0091] In the adhesive film 1, conductive particles 4 are dispersed in the first adhesive layer 2. Therefore, the adhesive film 1 is an anisotropically conductive adhesive film having anisotropic conductivity. The adhesive film 1 is interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and is used for thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.

[0092] The adhesive film 1 can suppress the flow of conductive particles that occurs during the manufacture of a circuit connection structure. In addition, the adhesive film 1 tends to suppress peeling at the interface between the circuit component and the circuit connection portion formed by the adhesive film, which occurs when the circuit connection structure is used in a high-temperature, high-humidity environment.

[0093] Although the adhesive film for circuit connection of this embodiment has been described above, the present invention is not limited to the above embodiment.

[0094] For example, the adhesive film for circuit connection may be composed of two layers, a first adhesive layer and a second adhesive layer, or may be composed of three or more layers including a layer other than the first adhesive layer and the second adhesive layer (for example, a third adhesive layer). The third adhesive layer may be a layer having a composition similar to that described above for the first adhesive layer or the second adhesive layer, and may be a layer having a thickness similar to that described above for the first adhesive layer or the second adhesive layer. The adhesive film for circuit connection may further include, for example, a third adhesive layer on the surface of the first adhesive layer opposite to the second adhesive layer. That is, the adhesive film for circuit connection is, for example, formed by laminating the second adhesive layer, the first adhesive layer, and the third adhesive layer in this order. In this case, the third adhesive layer is, for example, made of a thermosetting composition similar to the second adhesive layer.

[0095] Furthermore, although the adhesive film for circuit connection in the above embodiment is an anisotropic conductive adhesive film having anisotropic conductivity, the adhesive film for circuit connection may also be a conductive adhesive film that does not have anisotropic conductivity.

[0096] <Method of manufacturing an adhesive film for circuit connection> The manufacturing method of the adhesive film 1 for circuit connection of this embodiment includes, for example, a preparation step (first preparation step) of preparing the above-mentioned first adhesive layer 2, and a lamination step of laminating the above-mentioned second adhesive layer 3 on the first adhesive layer 2. The manufacturing method of the adhesive film 1 for circuit connection may further include a preparation step (second preparation step) of preparing the second adhesive layer 3.

[0097] In the first preparation step, for example, the first adhesive layer 2 is formed on a substrate to obtain a first adhesive film, thereby preparing the first adhesive layer 2. Specifically, first, the (A) component, the (B) component, the (C) component, and the (D) component, as well as other components added as necessary, are added to an organic solvent, and dissolved or dispersed by stirring, mixing, kneading, or the like, to prepare a varnish composition (varnish of a photo- and thermosetting composition). Thereafter, the varnish composition is applied to a substrate that has been subjected to a release treatment using a knife coater, a roll coater, an applicator, a comma coater, a die coater, or the like, and the organic solvent is volatilized by heating to form a layer made of a photo- and thermosetting composition on the substrate. Next, the layer made of a photo- and thermosetting composition is irradiated with light to cure (photo-cur) the photo- and thermosetting composition, and the first adhesive layer 2 is formed on the substrate (curing step). Thereby, a first adhesive film is obtained.

[0098] The organic solvent used in the preparation of the varnish composition is preferably one that has the property of dissolving or dispersing each component uniformly, and examples thereof include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These organic solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in the preparation of the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.

[0099] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the organic solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, and the like can be used.

[0100] The heating conditions for volatilizing the organic solvent from the varnish composition applied to the substrate are preferably conditions that allow the organic solvent to volatilize sufficiently, for example, at 40° C. or higher and 120° C. or lower for 0.1 minutes or longer and 10 minutes or shorter.

[0101] For the light irradiation in the curing step, it is preferable to use light having a wavelength in the range of 150 to 750 nm (for example, ultraviolet light). The light irradiation can be carried out using, for example, a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, or the like. The amount of light irradiation is not particularly limited, and for example, the integrated light amount of light having a wavelength of 365 nm is 100 mJ / cm. 2 or more, and 2 or more, and 2 The amount of light irradiation may be, for example, 10,000 mJ / cm2 in terms of the integrated light amount of light with a wavelength of 365 nm. 2 may be less than 5000 mJ / cm 2 or less than 3000 mJ / cm 2 It may be the following:

[0102] In the second preparation step, the second adhesive layer 3 is prepared by forming the second adhesive layer 3 on the substrate to obtain a second adhesive film in the same manner as in the first preparation step, except that the (a) and (b) components, as well as other components added as necessary, are used and light irradiation is not performed.

[0103] In the lamination step, the first adhesive film and the second adhesive film may be laminated on the first adhesive layer 2 to form a second adhesive layer 3, or the first adhesive layer 2 may be coated with a varnish composition (varnish of a thermosetting composition) obtained by using the (a) component and the (b) component, as well as other components added as necessary, and the organic solvent may be volatilized to laminate the second adhesive layer 3 on the first adhesive layer 2. The lamination step may be performed during the first preparation step. For example, after forming a layer made of a photo- and thermosetting composition, the lamination step may be performed to obtain a laminate including a layer made of a photo- and thermosetting composition (precursor of the first adhesive layer 2) and a layer made of a thermosetting composition (second adhesive layer 3). In this case, the layer made of a photo- and thermosetting composition may be cured by irradiating the obtained laminate with light, thereby completing the first preparation step.

[0104] Examples of the method for bonding the first adhesive film and the second adhesive film include hot pressing, roll lamination, vacuum lamination, etc. Lamination may be performed under temperature conditions of, for example, 0 to 80°C.

[0105] <Circuit connection structure and method for producing same> Hereinafter, a circuit connection structure using the above-mentioned adhesive film 1 for circuit connection as a circuit connecting material and a method for producing the same will be described.

[0106] Fig. 2 is a schematic cross-sectional view showing a circuit connection structure of one embodiment. As shown in Fig. 2, the circuit connection structure 10 includes a first circuit board 11 and a first circuit member 13 having a first electrode 12 formed on a main surface 11a of the first circuit board 11, a second circuit board 14 and a second circuit member 16 having a second electrode 15 formed on a main surface 14a of the second circuit board 14, and a circuit connection portion 17 disposed between the first circuit member 13 and the second circuit member 16, electrically connecting the first electrode 12 and the second electrode 15 to each other.

[0107] The first circuit member 13 and the second circuit member 16 may be the same or different from each other. The first circuit member 13 and the second circuit member 16 may be a glass substrate or a plastic substrate on which electrodes are formed, a printed wiring board, a ceramic wiring board, a flexible wiring board, a semiconductor silicon IC chip, or the like. The first circuit board 11 and the second circuit board 14 may be formed of an inorganic material such as a semiconductor, glass, or ceramic, an organic material such as polyimide or polycarbonate, or a composite material such as glass / epoxy, or the like. The first electrode 12 and the second electrode 15 may be formed of gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, indium tin oxide (ITO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), or the like. The first electrode 12 and the second electrode 15 may be a circuit electrode or a bump electrode. At least one of the first electrode 12 and the second electrode 15 may be a bump electrode. In FIG. 2, the second electrode 15 is a bump electrode.

[0108] The circuit connection portion 17 is made of the cured product of the adhesive film 1 described above. The circuit connection portion 17 has, for example, a first region 18 located on the first circuit member 13 side in the direction in which the first circuit member 13 and the second circuit member 16 face each other (hereinafter referred to as the "facing direction") and made of a cured product of components other than the conductive particles 4 of the photo- and heat-curable composition described above, a second region 19 located on the second circuit member 16 side in the facing direction and made of a cured product of the thermosetting composition described above, and conductive particles 4 interposed at least between the first electrode 12 and the second electrode 15 to electrically connect the first electrode 12 and the second electrode 15 to each other. The circuit connection portion does not have to have two regions like the first region 18 and the second region 19, and may be made of, for example, a cured product in which a cured product of components other than the conductive particles 4 of the photo- and heat-curable composition described above and a cured product of the thermosetting composition described above are mixed.

[0109] Fig. 3 is a schematic cross-sectional view showing a method for producing the circuit connection structure 10. As shown in Fig. 3, the method for producing the circuit connection structure 10 includes, for example, a step of interposing the above-mentioned adhesive film 1 between a first circuit member 13 having a first electrode 12 and a second circuit member 16 having a second electrode 15, and thermocompressing the first circuit member 13 and the second circuit member 16 to electrically connect the first electrode 12 and the second electrode 15 to each other.

[0110] Specifically, as shown in FIG. 3(a), first, a first circuit member 13 including a first circuit board 11 and a first electrode 12 formed on a main surface 11a of the first circuit board 11, and a second circuit member 16 including a second circuit board 14 and a second electrode 15 formed on a main surface 14a of the second circuit board 14 are prepared.

[0111] Next, the first circuit member 13 and the second circuit member 16 are arranged so that the first electrode 12 and the second electrode 15 face each other, and the adhesive film 1 is arranged between the first circuit member 13 and the second circuit member 16. For example, as shown in FIG. 3(a), the adhesive film 1 is laminated on the first circuit member 13 so that the first adhesive layer 2 side faces the mounting surface 11a of the first circuit member 13. Next, the second circuit member 16 is arranged on the first circuit member 13 on which the adhesive film 1 is laminated so that the first electrode 12 on the first circuit board 11 and the second electrode 15 on the second circuit board 14 face each other.

[0112] Then, as shown in Fig. 3(b), the first circuit member 13, the adhesive film 1, and the second circuit member 16 are heated while the first circuit member 13 and the second circuit member 16 are pressed in the thickness direction to thermocompress the first circuit member 13 and the second circuit member 16 together. At this time, as shown by the arrow in Fig. 3(b), the second adhesive layer 3 is made of a flowable uncured thermosetting composition, so that it flows to fill the gap between the second electrodes 15, 15 and is cured by the heating. As a result, the first electrode 12 and the second electrode 15 are electrically connected to each other via the conductive particles 4, and the first circuit member 13 and the second circuit member 16 are bonded to each other, thereby obtaining the circuit connection structure 10 shown in Fig. 2. In the manufacturing method of the circuit connection structure 10 of this embodiment, the first adhesive layer 2 is a pre-cured layer, so that the conductive particles 4 are fixed in the first adhesive layer 2, and the first adhesive layer 2 hardly flows during the thermocompression bonding, so that the conductive particles are efficiently captured between the opposing electrodes, thereby reducing the connection resistance between the opposing electrodes 12 and 15. As a result, a circuit connection structure with excellent connection reliability can be obtained.

[0113] <Adhesive film storage set> Fig. 4 is a perspective view showing an adhesive film storage set of one embodiment. As shown in Fig. 4, the adhesive film storage set 20 includes an adhesive film for circuit connection 1, a reel 21 around which the adhesive film 1 is wound, and a storage member 22 for storing the adhesive film 1 and the reel 21.

[0114] As shown in Fig. 4, the adhesive film 1 is, for example, in the form of a tape. The tape-shaped adhesive film 1 is produced, for example, by cutting a sheet-shaped raw material into a long piece with a width according to the intended use. A substrate may be provided on one side of the adhesive film 1. The substrate may be the above-mentioned PET film or the like.

[0115] The reel 21 includes a first side plate 24 having a winding core 23 around which the adhesive film 1 is wound, and a second side plate 25 arranged to face the first side plate 24 with the winding core 23 in between.

[0116] The first side plate 24 is, for example, a disk made of plastic, and has an opening with a circular cross section provided in the center portion of the first side plate 24.

[0117] The winding core 23 of the first side plate 24 is a portion around which the adhesive film 1 is wound. The winding core 23 is made of, for example, plastic, and has a circular shape with a thickness similar to the width of the adhesive film 1. The winding core 23 is fixed to the inner surface of the first side plate 24 so as to surround the opening of the first side plate 24. The reel 21 is provided at its center with a shaft hole 26 into which a rotating shaft of a winding device or a pay-out device (not shown) is inserted. When the rotating shaft of the winding device or the pay-out device is inserted into the shaft hole 26 and the rotating shaft is driven, the reel 21 rotates without spinning freely. A desiccant container containing a desiccant may be fitted into the shaft hole 26.

[0118] The second side plate 25, like the first side plate 24, is a circular plate made of, for example, plastic, and a central portion of the second side plate 25 is provided with an opening having a circular cross-section and the same diameter as the opening of the first side plate 24.

[0119] The storage member 22 is, for example, bag-shaped, and stores the adhesive film 1 and the reel 21. The storage member 22 has an insertion opening 27 for storing (inserting) the adhesive film 1 and the reel 21 inside the storage member 22.

[0120] The storage member 22 has a visual confirmation portion that allows the inside of the storage member 22 to be visually confirmed from the outside. The storage member 22 shown in FIG.

[0121] The visual confirmation section 28 is transparent to visible light. For example, when the light transmittance in the visual confirmation section 28 is measured in the wavelength range of 450 to 750 nm, there is at least one region with a wavelength width of 50 nm between the wavelengths of 450 to 750 nm, in which the average light transmittance is 30% or more. The light transmittance of the visual confirmation section 28 is obtained by preparing a sample by cutting the visual confirmation section 28 to a predetermined size and measuring the light transmittance of the sample with an ultraviolet-visible spectrophotometer. Since the storage member 22 has such a visual confirmation section 28, various information such as the product name, lot number, and expiration date attached to, for example, the reel 21 inside the storage member 22 can be confirmed from the outside of the storage member 22. This is expected to prevent mixing of different products and to make the sorting work more efficient.

[0122] The transmittance of light having a wavelength of 365 nm in the visual observation portion 28 is 10% or less. Since the transmittance of light having a wavelength of 365 nm in the visual observation portion 28 is 10% or less, it is possible to suppress the curing of the thermosetting composition caused by the light incident from the outside to the inside of the housing member 22 and the photopolymerization initiator remaining in the first adhesive layer 2. As a result, it is possible to maintain the effect of reducing the connection resistance of the adhesive film 1, and when the adhesive film 1 is used to connect circuit members, it is possible to reduce the connection resistance between opposing electrodes. From the viewpoint of further suppressing the generation of radicals from the photopolymerization initiator, the transmittance of light having a wavelength of 365 nm in the visual observation portion 28 is preferably 10% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.1% or less.

[0123] From the same viewpoint, the maximum transmittance of light in the wavelength region capable of generating radicals, cations or anions from the above-mentioned photopolymerization initiator (component (B)) in visualizing portion 28 is preferably 10% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.1% or less. Specifically, the maximum transmittance of light in the wavelength range of 254 to 405 nm in visualizing portion 28 is preferably 10% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.1% or less.

[0124] The visual confirmation section 28 (housing member 22) is formed of a sheet having a thickness of, for example, 10 to 5000 μm. The sheet is made of a material that has a transmittance of 10% or less for light having a wavelength of 365 nm in the visual confirmation section 28. Such a material may be made of one type of component or may be made of multiple types of components. Examples of such materials include low-density polyethylene, linear low-density polyethylene, polycarbonate, polyester, polyacrylate, polyamide, glass, and the like. These materials may contain an ultraviolet absorbing agent. The visual confirmation section 28 may have a layered structure formed by laminating multiple layers having different light transmittances. In this case, each layer constituting the visual confirmation section 28 may be made of the above-mentioned material.

[0125] The insertion opening 27 may be sealed by being closed, for example, by a sealer, to prevent air from entering from the outside when the reel 21 is stored. In this case, it is preferable to remove the air from inside the storage member 22 by suction before closing the insertion opening 27. This is expected to reduce the humidity inside the storage member 22 from the initial stage of storage, and to prevent air from entering from the outside. In addition, by closely contacting the inner surface of the storage member 22 with the surface of the reel 21, it is possible to prevent the generation of foreign matter due to rubbing between the inner surface of the storage member 22 and the surface of the reel 21 caused by vibration during transportation, and to prevent damage to the outer surfaces of the side plates 24, 25 of the reel 21.

[0126] In the above embodiment, the housing member is configured so that the entire housing member is the visual confirmation portion, but in another embodiment, the housing member may have a visual confirmation portion in a part of the housing member. For example, the housing member may have a rectangular visual confirmation portion in approximately the center of a side surface of the housing member. In this case, the portion of the housing member other than the visual confirmation portion may be black so as not to transmit, for example, ultraviolet light and visible light.

[0127] In the above embodiment, the shape of the container is a bag, but the container may be, for example, a box. It is preferable that the container has a notch for opening. In this case, the container can be easily opened when in use. EXAMPLES

[0128] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0129] <Synthesis of polyurethane acrylate (UA1)> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours under air atmosphere. This resulted in polyurethane acrylate (UA1). The weight-average molecular weight of polyurethane acrylate (UA1) was 15,000. The weight-average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min

[0130] <Preparation of conductive particles> A layer of nickel was formed on the surface of the polystyrene particles to a thickness of 0.2 μm, thus obtaining conductive particles with an average particle size of 4 μm, a maximum particle size of 4.5 μm, and a specific gravity of 2.5.

[0131] <Method for preparing polyester urethane resin> 48 parts by mass of isophthalic acid and 37 parts by mass of neopentyl glycol were put into a stainless steel autoclave equipped with a stirrer, a thermometer, a condenser, a vacuum generator, and a nitrogen gas inlet tube, and 0.02 parts by mass of tetrabutoxy titanate as a catalyst was further put in. Then, the temperature was raised to 220°C under a nitrogen stream, and the mixture was stirred for 8 hours. Then, the pressure was reduced to atmospheric pressure (760 mmHg), and the mixture was cooled to room temperature. This caused a white precipitate to precipitate. Next, the white precipitate was taken out, washed with water, and then vacuum dried to obtain a polyester polyol. The obtained polyester polyol was thoroughly dried, and then dissolved in MEK (methyl ethyl ketone), and put into a four-neck flask equipped with a stirrer, a dropping funnel, a reflux condenser, and a nitrogen gas inlet tube. Furthermore, dibutyltin laurate was added as a catalyst in an amount of 0.05 parts by mass per 100 parts by mass of polyester polyol, and 4,4'-diphenylmethane diisocyanate in an amount of 50 parts by mass per 100 parts by mass of polyester polyol was dissolved in MEK and added using a dropping funnel, and the mixture was stirred at 80°C for 4 hours to obtain the desired polyester urethane resin.

[0132] <Preparation of Varnish of Photo- and Thermosetting Composition (Varnish Composition)> The components shown below were mixed in the amounts (parts by mass) shown in Table 1 to prepare varnishes of photo- and thermosetting compositions 1 to 8.

[0133] (polymerizable compound) A1: Dicyclopentadiene diacrylate (product name: DCP-A, manufactured by Toagosei Co., Ltd.) A2: Polyurethane acrylate (UA1) synthesized as described above A3: 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.) (Photopolymerization initiator) B1: 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyloxime)] (trade name: Irgacure (registered trademark) OXE01, manufactured by BASF) B2: Ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime) (trade name: Irgacure (registered trademark) OXE02, manufactured by BASF) (Thermal polymerization initiator) C1: Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation) (Conductive particles) D1: Conductive particles prepared as described above (thermoplastic resin) E1: Polyester urethane resin synthesized as described above (Coupling Agent) F1: 3-methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.) (filling material) G1: Silica fine particles (product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm) (solvent) H1: Methyl ethyl ketone

[0134] [Table 1]

[0135] <Preparation of Thermosetting Composition Varnish (Varnish Composition)> The polymerizable compounds a1 to a3, the thermal polymerization initiator b1, the coupling agent f1, the filler g1 and the solvent h1 used were the same as the polymerizable compounds A1 to A3, the thermal polymerization initiator C1, the coupling agent F1, the filler G1 and the solvent H1 in the photo- and thermosetting composition, and the thermoplastic resin e1 used was the component shown below. These components were mixed in the amounts (parts by mass) shown in Table 2 to prepare a varnish of the thermosetting composition 1. (thermoplastic resin) e1: Phenoxy resin (product name: PKHC, manufactured by Union Carbide)

[0136] [Table 2]

[0137] Example 1 [Preparation of the first adhesive film] The varnish of the photo- and thermosetting composition 1 was applied onto a PET film having a thickness of 50 μm using a coating device. Then, hot air drying was performed at 70° C. for 3 minutes to form a layer of the photo- and thermosetting composition 1 having a thickness (thickness after drying) of 4 μm on the PET film. The thickness was measured using a contact thickness meter. Note that the size of the conductive particles is reflected when using a contact thickness meter, and the thickness of the region where the conductive particles are present is measured. Therefore, after laminating the second adhesive layer to prepare a two-layer circuit connection adhesive film, the thickness of the first adhesive layer located in the space between adjacent conductive particles was measured by the method described below.

[0138] Next, the layer made of the photo- and thermosetting composition 1 was irradiated with a metal halide lamp at an integrated light dose of 1500 mJ / cm 2 2 The polymerizable compound was polymerized by irradiating the film with light so that the photo- and thermosetting composition 1 was cured to form a first adhesive layer. The above operations resulted in a first adhesive film (thickness of the region where the conductive particles were present: 4 μm) having a first adhesive layer on the PET film. The conductive particle density at this time was approximately 7000 pcs / mm 2 It was.

[0139] [Preparation of the second adhesive film] The varnish of the thermosetting composition 1 was applied onto a PET film having a thickness of 50 μm using a coating device. Then, hot air drying was performed at 70° C. for 3 minutes to form a second adhesive layer (a layer made of the thermosetting composition 1) having a thickness of 8 μm on the PET film. Through the above operations, a second adhesive film having a second adhesive layer on the PET film was obtained.

[0140] [Preparation of adhesive film for circuit connection] The first adhesive film and the second adhesive film were arranged so that their adhesive layers faced each other, and were laminated with a roll laminator while being heated together with the PET film substrate at 40° C. This produced a two-layer adhesive film for circuit connection in which the first adhesive layer and the second adhesive layer were laminated.

[0141] The thickness of the first adhesive layer of the prepared circuit connection adhesive film was measured by the following method. First, the circuit connection adhesive film was sandwiched between two pieces of glass (thickness: about 1 mm) and cast with a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: JER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a hardener (product name: Epomount hardener, manufactured by Refine Tech Co., Ltd.). Then, the cross section was polished using a polishing machine, and the thickness of the first adhesive layer located in the space between adjacent conductive particles was measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Co., Ltd.). The thickness of the first adhesive layer was 2 μm.

[0142] [Fabrication of circuit connection structure] A 25 μm pitch COF (manufactured by FLEXSEED Co., Ltd.) and a glass substrate (manufactured by Geomatec Co., Ltd.) with a thin-film electrode (height: 1200 Å) made of amorphous indium tin oxide (ITO) on the glass substrate were connected over a width of 1 mm using a thermocompression bonding device (heating method: constant heat type, manufactured by Taiyo Kikai Seisakusho Co., Ltd.) under conditions of 170° C., 6 MPa, and 4 seconds to produce a circuit connection structure (connection structure). Note that, when connecting, the circuit connection adhesive film was placed on the glass substrate so that the surface of the first adhesive layer side of the circuit connection adhesive film faced the glass substrate.

[0143] <Evaluation of circuit connection structure> [Evaluation of particle flowability] The obtained circuit connection structure was evaluated for particle flow state in the resin seepage portion of the circuit connection adhesive film using a microscope (product name: ECLIPSE L200, manufactured by Nikon Corporation). Specifically, the produced circuit connection structure was observed with a microscope from the glass substrate side, and the particle state of the portion that seeped out beyond the width of the circuit connection adhesive film was evaluated on a three-level scale. A state in which the particles barely moved and there were no particles in the seepage portion was rated as 1, a state in which the particles moved slightly but no connection between the particles was observed was rated as 2, and a state in which the particles flowed and connections between the particles were observed was rated as 3.

[0144] [Connection resistance evaluation] The connection resistance between the opposing electrodes of the obtained circuit connection structure was measured with a multimeter immediately after connection and after a high-temperature, high-humidity test. The high-temperature, high-humidity test was performed by leaving the structure in a constant temperature and humidity chamber at 85°C and 85% RH for 200 hours. The connection resistance was calculated as the average value of 16 resistance points between the opposing electrodes.

[0145] [Peeling evaluation] The presence or absence of peeling at the circuit connection part of the circuit connection structure after the high temperature and high humidity test was evaluated using a microscope (product name: ECLIPSE L200, manufactured by Nikon Corporation). Specifically, the circuit connection structure prepared as described above was observed with a microscope from the glass substrate side, and the peeling state between the glass substrate and the circuit connection adhesive film was evaluated in three stages. The percentage of the total area of ​​the circuit connection adhesive film that was peeled off from the glass substrate was determined, and A was used for almost no peeling (the percentage of peeled parts was less than 5% of the total), B for a small amount of peeling (the percentage of peeled parts was 5% or more but less than 20% of the total), and C for peeling (the percentage of peeled parts was 20% or more of the total).

[0146] (Examples 2 to 7 and Comparative Example 1) Except for using photo- and thermosetting compositions 2 to 8 as the photo- and thermosetting compositions, adhesive films for circuit connection and circuit connection structures were prepared in the same manner as in Example 1, and the circuit connection structures were evaluated in the same manner as in Example 1. The results are shown in Tables 3 and 4.

[0147] [Table 3]

[0148] [Table 4] [Explanation of symbols]

[0149] 1...adhesive film for circuit connection, 2...first adhesive layer, 3...second adhesive layer, 4...conductive particles, 10...circuit connection structure, 12...circuit electrode (first electrode), 13...first circuit member, 15...bump electrode (second electrode), 16...second circuit member, 20...adhesive film storage set, 22...storage member, 28...visible portion.

Claims

1. A first adhesive layer and a second adhesive layer laminated on the first adhesive layer, the first adhesive layer is made of a photocured product of a photo- and thermosetting composition containing a polymerizable compound, a photopolymerization initiator, a thermal polymerization initiator, and conductive particles; The second adhesive layer is made of a thermosetting composition.

2. 2. The adhesive film for circuit connection according to claim 1, wherein the polymerizable compound is a radically polymerizable compound having a radically polymerizable group.

3. 3. The adhesive film for circuit connection according to claim 1, wherein the polymerizable compound contains a radical-polymerizable compound having a phosphate ester structure represented by the following formula (1): 【Chemistry 1】 [In formula (1), n ​​represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.]

4. 4. The adhesive film for circuit connection according to claim 1, wherein the thermosetting composition contains a radically polymerizable compound having a radically polymerizable group.

5. The adhesive film for circuit connection according to any one of claims 1 to 4, wherein the photopolymerization initiator has a structure represented by the following formula (I): 【Chemistry 2】

6. 6. The adhesive film for circuit connection according to claim 5, wherein the structure represented by formula (I) is an oxime ester structure, a bisimidazole structure or an acridine structure.

7. 7. The adhesive film for circuit connection according to claim 1, wherein the photopolymerization initiator contains a compound having a structure represented by the following formula (VI): 【Chemistry 3】 [In formula (VI), R 11 , R 12 and R 13 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing an aromatic hydrocarbon group.

8. 8. The adhesive film for circuit connection according to claim 1, wherein the thickness of the first adhesive layer is 0.1 to 0.8 times the average particle size of the conductive particles.

9. providing a first adhesive layer; and a lamination step of laminating a second adhesive layer made of a thermosetting composition on the first adhesive layer, The method for manufacturing an adhesive film for circuit connection, wherein the preparation process includes a step of irradiating light to a layer consisting of a photo- and thermosetting composition containing a polymerizable compound, a photopolymerization initiator, a thermal polymerization initiator, and conductive particles, thereby curing the photo- and thermosetting composition to obtain the first adhesive layer.

10. The method for producing an adhesive film for circuit connection according to claim 9 , wherein the polymerizable compound is a radically polymerizable compound having a radically polymerizable group.

11. The method for producing an adhesive film for circuit connection according to claim 9 or 10, wherein the thermosetting composition contains a radically polymerizable compound having a radically polymerizable group.

12. The method for producing an adhesive film for circuit connection according to any one of claims 9 to 11, wherein the thickness of the first adhesive layer is 0.1 to 0.8 times the average particle size of the conductive particles.

13. 9. A method for producing a circuit connection structure, comprising the steps of: interposing an adhesive film for circuit connection according to any one of claims 1 to 8 between a first circuit member having a first electrode and a second circuit member having a second electrode; and thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other.

14. An adhesive film for circuit connection according to any one of claims 1 to 8, and a housing member for housing the adhesive film, the storage member has a visual confirmation portion that allows the inside of the storage member to be visually confirmed from the outside, The adhesive film storage set has a transmittance of 10% or less for light having a wavelength of 365 nm in the visible portion.

Citation Information

Patent Citations

  • Curable resin composition

    JP2001106735A

  • Adhesive having anisotropic electric conductivity

    JP2002285128A

  • Liquid thermosetting resin composition and copper-clad laminated plate using the same

    JP2010018778A

  • Connection method, connection structure, anisotropic conductive film and method for producing the anisotropic conductive film

    JP2013125858A

  • Anisotropic conductive film and method for producing the same

    JP2014043574A